Evaluation on the implementation of Executive Order No. 305: Devolving Fishing Vessels Registration in the Province of Albay - Ayende, Larry; Macabeo, Manny (JPAIR Multidisciplinary Research, 2025)
Executive Order No. 305 aims to improve fisheries management by devolving the registration of small fishing vessels to local government units. This aims to increase transparency in vessel activity and facilitate better monitoring and enforcement of fisheries regulations. This study evaluates the implementation of the PNP Maritime Unit on Executive Order No. 305 in Devolving Fishing Vessels Registration in the province of Albay in terms of Registration and Licensing, Adherence to Safety Standards, Collaboration Mechanism, and Monitoring and Evaluation System. Likewise, it identified the bottlenecks faced by the PNP Maritime Unit in the implementation of Executive Order 305 in the Province of Albay. This study used the Descriptive Quantitative Research Design. The respondents of the study are the Regional Maritime Unit 5 personnel, Local Government Unit, Barangay Fisheries and Aquatic Resources Management, and selected Fisherfolk in Tabaco City and Legazpi City. There is a consensus among stakeholders on the importance of the devolution process, safety standards, collaboration mechanisms, and monitoring and evaluation systems. Addressing challenges like capacity building, resources, infrastructure, and coordination is important to successfully implement EO 305 for sustainable fisheries. The PNP, LGU, BFAR, and fisherfolk may continue collaborating and sharing best practices to optimize the devolved fishing vessel registration by addressing challenges and investing in capacity building. They prioritize capacity building, resource allocation, and public awareness to achieve sustainable fisheries management and protect livelihoods.
Keywords: Social Science; Implementation; Devolving; Fishing Vessel; Registration; descriptive quantitative; Philippines